1990
DOI: 10.1113/jphysiol.1990.sp018102
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cold‐induced thermogenesis in full‐term pregnant rats.

Abstract: SUMMARY1. Thermoregulation against cold exposure was studied in rats during pregnancy and early lactation, and compared with that of virgin rats.2. When exposed to 0 TC for 60 min, rats which were within 24-48 h of parturition (pre-1-day rats) and those within 24 h of parturition (pre-0-day rats) showed significantly larger falls of colonic temperature (To) than virgin rats. The temperature decrease was greatest in the pre-0-day rats, being 4' 1 + 0 4 0C (mean + S.E.M.) at the end of cold exposure, compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…In keeping with this idea, thermogenic responses to cold are reduced in full‐term pregnant rats. 41 Similarly, pressor and tachycardic responses recorded in our laboratory following icv PGE 2 are reduced at the same time that febrile responses are reduced. As fever is brought about mainly by sympathetic activation, the reduction of fever at term may be a reflection of reduced sympathetic drive or response at this time.…”
Section: Fever In Pregnant Parturient and Lactating Ratsmentioning
confidence: 85%
“…In keeping with this idea, thermogenic responses to cold are reduced in full‐term pregnant rats. 41 Similarly, pressor and tachycardic responses recorded in our laboratory following icv PGE 2 are reduced at the same time that febrile responses are reduced. As fever is brought about mainly by sympathetic activation, the reduction of fever at term may be a reflection of reduced sympathetic drive or response at this time.…”
Section: Fever In Pregnant Parturient and Lactating Ratsmentioning
confidence: 85%
“…Inhibition of cold-induced thermogenesis in late-pregnant rats has also been reported [6]. This diminished thermogenic activity is related to lowered levels of UCP1 expression and GDPbinding activity [7,8], as well as decreased lipoprotein 204 lipase and iodothyronine 5'-deiodinase activity levels [9].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the fever suppression seen at the lower dose is a specific deficit in fever mechanisms or represents a more generalized thermoregulatory deficit is not known. However, it has been reported that rats in late pregnancy are less able to maintain their body temperature during acute cold exposure than are middle term or post partum rats (48). Brown adipose tissue activity, which is important in fever thermo-genesis (49,50) also declines in late pregnancy, but its further decrease during lactation, (when we are able to obtain fever) make this an unlikely candidate (51).…”
Section: Discussionmentioning
confidence: 96%